Ensinar a esquecer - ensino de história e extrema direita - Karla Saraiva; Fernando Seffner (Universidade Estadual de Maringá, 2023)
The article aims to analyze how the extreme right wing has sought to transform the teaching of history, displacing it from academically accepted historiography to glorious narratives in the form of a national tale (Citron, 2017). The research is based on a theoretical framework built with the contribution of several authors, with emphasis on Cesarino (2022), Nunes (2022), Pelbart (2019), Traverso (2021), Stanley (2020). After presenting an overview of the rise of the extreme right in Brazil and the world, we analyze documents from the French and American extreme right that propose changes in history teaching. Then, we discuss the productions of Brasil Paralelo in the form of public history and we tension this version from an ethnographic study of school culture. The article shows approximations between the historiographical forms and the methods of dissemination of the proposals by the extreme right in the three countries, but also indicates some departures.